EROSI PADA BEBERAPA PENGGUNAAN LAHAN DI SUB DAS OLONJONGE KABUPATEN PARIGI MOUTONG SULAWESI TENGAH - Alfreds Patodo; Herman Harijanto; Abdul Wahid (Universitas Tadulako, 2018)
The land has great potential in supporting human life activities. Human dependence on land resources which continues to increase as the number of population that causing the increase of population pressure to land resources so that land use is very difficult to avoid, as well as happening of land use in Das Olonjonge of Parigi Moutong District of Central Sulawesi. This study aims to find out a scale of erosion and surface runoff of some land using in the regions of DAS Olonjonge. This study was conducted in June 2015 until November 2015. This study was conducted in DAS Olonjonge sub-district in the area of the research 3.391,43 Ha. Administratively, the research area is located in South Parigi Sub-District, Parigi Moutong District, Central Sulawesi. This research used methods of measuring and collecting data, by placing the plot of 20 m x 4 m size that was put in some lands use. The result of this study was analyzed in Laboratory at Forestry Faculty of Tadulako University. Of the three land cover conditions, the largest soil erosion can be found on mountainous terrain types (plot 1) with the weight of the soil mass eroded is 2.388,79 gram or 796,26 kg/ha and the smallest on the use of peanut lands type (plot 2) is 818,48 gram or 272,83 kg/ha. The largest surface of volume runoff is found on terrain land with an average value 33,64 liter or 11,21 m3/ha and the smallest on the peanut land which has the average value of runoff volume is 19,23 liter or 5,41 m3/ha.Keywords: Erosion, Surface Runoff, DAS